Al-Hadith Al-Gharib in the Discourse of Hadith Studies; The Authenticity and The Authority - Abdul Kamil (Universiti Sains Islam Malaysia, 2025)
Journal Of Hadith Studies, Volume 9 Issue 2 Page (136-145)